Advances in Biased Opioid Agonists for Analgesia: Side Effects Minimisation and Addiction Prevention - Zhang, Kaiyun (International Journal of Public Health and Medical Research, 2025)
Opioids, as frontline analgesics, are associated with substantial adverse effects. For example, μ-opioid receptor agonists commonly cause respiratory depression and carry high addictive potential, while κ-opioid receptor agonists can produce depression-like reactions and aversion. The introduction of biased agonism has offered a strategy to dissociate opioid-induced adverse effects from analgesic efficacy. In recent years, biased agonists developed for different opioid receptor types have shown promise in reducing side effects, lowering addictive liability, and achieving analgesia with improved therapeutic windows, suggesting the possibility of a safer next generation of analgesics. However, important obstacles and challenges remain.